The Treatment of Irony to Approximate Events - Eshboyeva Shoira (Genius Journals, 2023)
Any event is evaluated on the basis of the attitude towards others. Irony as a stylistic phenomenon, on the one hand, a reaction to irony (irony), metaphor, metonymy, synecdoche, epithet, simile, sarcasm, periphrasis, exaggeration, litota, allegory, symbol, revitalization, apostrophe. shows its essence based on.
Keywords: metaphor; metonymy; synecdoche; epithet